Effectiveness and Tolerability of Febuxostat vs Allopurinol in patients with Chronic Kidney Disease (CKD) on Conservative Therapy - Filomena Panza; Chiara Ralli; Ennio Duranti (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Uric  Acid  appears  to  be  one  of  the  most  important  prognostic  markers  and  one  of  the  principal  risk  factors  for  cardiovascular  diseases.  The  aim  of  our  study  was  to  assess  three  groups  of  patients: a first  group  treated  with  Allopurinol  (AL),  a  second  group  not  adequately  controlled  by  treatment  with AL  or  allergic  to  AL  switched  to  treatment  with  Febuxostat  (AL/FB)  and  a  third  group  of  naive  patients immediately treated with Febuxostat (FB). The effectiveness and tolerability of both drugs were therefore assessed over time. Materials and methods: 44 patients, with CKD in conservative therapy, were divided into 3 groups. A group of 20 patients (AL) with well controlled uricemic values (serum uric acid < 6 mg/dl); a group of 12 patients  (AL/FB)  with  not  well  controlled  uricemic  values  (serum  uric  acid  concentration  >  6.0  mg  /  dl) and / or intolerant to AL that were switched to treatment with FB, then a group of 12 naive patients (FB) treated immediately with FB. At time 0,3,6,9,12,18,24 months, all patients were monitored as regards: serum uric acid, renal function parameters, serum electrolytes, hemoglobin, lipid profile, blood glucose, glycated hemoglobin, proteinuria 24 hours,parathyroid hormone (PTH), C Reactive Protein (CRP). The doses of anti-uric acid administered drug were also evaluated. All the patients underwent a monitoring of blood pressure (BP), heart rate (HR) and body mass index (BMI).